Mapping Publication of Harassment in Sport: Bibliometric Analysis - Prabowo, Indra; Hendrayana, Yudy; Ma’mun, Amung; Berliana, Berliana; Sofyan, Davi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
This study aims to examine the evolution of scientific publications related to harassment in sports in the Scopus database using various bibliometric indicators such as publication trends, most active countries, scientific sources, top cites, and author keywords. From 1968 to 2022, the Scopus database recorded 1,721 publications related to harassment in sports. This review details bibliographic results using Microsoft Excel, Publish or Perish (PoP), and VOSviewer. Research findings indicate that between 1968 and 2005, publications followed a fluctuating trend. Since 2011, publications have increased to over 60 documents. 2021 will be the peak of publication with 221 documents. The International Review for the Sociology of Sport is the most active scientific source because it has published 40 documents. Leeds Beckett University, United Kingdom, became the most active institution with 37 documents. This study has several limitations; the method applied in this research needs to clarify how to find, categorize, and use databases. It should be noted that data can also be obtained from other databases. This bibliometric analysis provides important information regarding future research directions in sports harassment studies, which can be learned further by examining trending keywords.